Linear algebra : Pure & applied - Goodaire, Edgar G. (Singapore World Scientific Publishing Company, 2014)
This book offers a matrix-oriented approach to linear algebra, covering both introductory and advanced topics such as the pseudoinverse and singular value decomposition. It begins with the geometry of Euclidean 3-space to ground key concepts in a tangible context. While maintaining mathematical rigor, the focus on matrices and systems like Ax = b keeps the material accessible and practical. Applications play a central role, featuring examples from coding theory, least squares, electric circuits, Markov chains, and computer graphics.
Includes bibliographical references and index
Keywords: Cơ bản - Toán học